United States. Army. 92nd Infantry Division collection - United States. Army. Infantry Division, 92nd.; Ninety-Second Infantry Division World War II Association
Records of the U.S. Army 92nd Infantry Division and Ninety-Second Infantry Division World War II Association including correspondence, subject files, newspapers, newspaper clippings, exhibition material, posters, photograph albums, photographs, and other records relating chiefly to the service of the division during World War II, chiefly in the Italian campaign, 1943-1945. Subjects include African American military and civilian experience during World War II and the postwar era. Includes the association's newsletter, The Buffalo, and material pertaining to Lawnside, N.J., an incorporated African American town. Correspondents include Richard H. Kohn, Barry R. McCaffrey, Spencer Moore, A. William Perry, Colin L. Powell, and Hiram L. Tanner.
African American infantry division of the U.S. Army during World War I and World War II. Also known as the Buffalo Soldiers Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Kohn, Richard H. -- Correspondence; McCaffrey, Barry R. -- Correspondence; Moore, Spencer, -- 1921- -- Correspondence; Perry, A. William, -- 1924- -- Correspondence; Powell, Colin L. -- Correspondence; Tanner, Hiram L. -- Correspondence; African Americans -- Social conditions -- 20th century; African Americans -- New Jersey -- Lawnside; World War, 1939-1945 -- African Americans; World War, 1939-1945 -- Participation, African American; World War, 1939-1945 -- Campaigns -- Italy; Lawnside (N.J.) -- History; United States -- Armed Forces -- African Americans; Buffalo (Newsletter)